Vitamin D status among overweight and obese adolescents - Kumar Saurabh; Jyoti Bala; Hemang (Biomedical and Biotechnology Research Journal, 2020)
Introduction: Deficiency of vitamin D is pandemic and has been associated with a wide variety of disease states such as cardiovascular disease risk factors and impaired glucose homeostasis and are more common in overweight and obese children. Both endocrine and metabolic disorders occur with obesity and it has been suggested that obesity is a risk factor for vitamin D deficiency. The inverse association between higher body fat and lower vitamin D levels has been attributed to sequestration of the fat soluble vitamins within the plentiful adipose tissue. Aim and Objective: This study aims to determine the status of vitamin D levels in overweight and obese adolescent children and to compare them with age and sex matched healthy controls. Materials and Methods: This observational study was conducted in the Department of Biochemistry in collaboration with Department of Pediatrics, Pt. B.D. Sharma, PGIMS, Rohtak. Twenty-five overweight and obese adolescents based on BMI were recruited in study group (Group II) and twenty-five age and sex matched healthy controls were included in group I (Control group). Study samples were drawn and serum vitamin D levels were analyzed by radioimmunoassay. Results: Out of 25 cases 12(48%) were overweight and 13(52%) were obese adolescents. Mean BMI in group I was 17.36±3.67 kg/m2 and in group II was 31.90±1.01 kg/m2. 14 (56%) had vitamin D levels <20 ng/mL that is in the deficiency range. 7 (28%) had in the insufficiency range (21-30 ng/mL), 4 (16%) had in the sufficient range. Mean serum vitamin D levels in group I (Controls) were 28.41±8.83 and group II (Cases) were 21.6 ±5.65. The serum vitamin D levels were significantly decreased in group II as compared to group I (p = 0.002). Conclusion: The findings of present study concluded that, vitamin D deficiency is common problem obese and overweight adolescents, this may help to explain the relationship between obesity and several chronic diseases that are associated with poor Vitamin D status. However, there is a need for more randomized controlled trials, involving larger sample sizes, focusing on obese adolescents with documented vitamin D deficiency and careful selection of the dose, dosing regimen, and achievement of vitamin D concentrations.